Multi-objective model predictive control method for T-type three-level grid-connected - Pan Ning; Xie Zhen; Mo Jiaqing; Wang Yuanhao (E3S Web of Conferences, 2023)
Based on the mathematical model of T-type three-level topology, a T-type three-level inverter model is proposed to predict the multi-objective control method, which mainly includes DC neutral voltage (NP-V), switching state, inverter voltage vector, and multi-objective cost function. Different emphases can be selected according to the application requirements, and coordinated control of different control objectives can be realized by giving different weight values to different control objectives. An extended observer (ESO) is added to observe the error part of the grid-connected inverter system, and the observed results are compensated to the grid-connected reference voltage. The simulation results show that the total harmonic distortion rate of the output current of the inverter is lower than that of the traditional finite control set model predictive control strategy. In addition, the proposed method can realize the balance control of the midpoint potential, and the principle is simple.